Selection and preparation of cassava cuttings for planting - Lozano, J.C.; Toro, Julio C.; Castro Merino, A.; Bellotti, Anthony C.; Ceballos, L.F.; Fernández, F.O. (International Center for Tropical Agriculture, 1984)
Study guide to be used as a supplement to the audiotutorial unit on the same topic.